CHEMICAL CHARACTERISATION OF BHUIAVALI (Phyllanthus niruri) - Phadnis, A.D. (Medknow Publications & Media Pvt Ltd, 1995)
The present article describes the chemical characteristics such as pH of aqueous extract, fluorescence, aqueous and alcoholic extractives, lignans and TLC profile of aqueous extract of Bhuiavli (Phyllanthus niruri).